Figurative Language and Imagery Analysis on “I Wandered Lonely As a Cloud” By William Wordsworth: Semantics Study - Chintiya Veronika; Ida Zuraida (Budapest International Research and Critics University, 2022)
This study’s aim is to analyze and examine the types figurative language and imagery that consist in the poem. The analysis used a descriptive qualitative research method. The data used were taken from I Wandered Lonely As A Cloud book by William Wordsworth. The result demonstrates that there are four types of figurative language occurs found; 23% occurrence of comparison, 10% occurrence of contradiction, 10% occurrence of correlations, and 16% occurrence of repetition figurative language. Also, there are two types of imagery found; percentage occurrence of visual imagery is 47% while kinesthetic imagery is 10%. According to the findings of this analysis, figurative language occurs frequently in the type of comparison for percentage of 23% and visual imagery with 47% occurrence.